PERTUMBUHAN RUMPUT ODOT DI BAWAH PENGARUH KOMBINASI PUPUK - Adi Fathul Qohar; Bahrun; Nur Hidayat; Nunur Nuraeni (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
The purpose of the study was determined the optimum level of manure and NPK combination in terms of growth namely, wheight plant and number of leaves of dwarf grass. The material used in the study was the third defoliation dwarf grass plant which was initially planted in a total area of ??278 m2 with an area of ??each plot or unit of 5 m2 and a spacing of 0.75 mx 0.35 m so that 720 stems of dwarf grass cuttings were needed, 270 kg of manure, 2.5 kg of NPK fertilizer. The method used was factorial pattern experiment with a randomized blok design. The first factor was manure consisting of K0: manure 0 kg/5m2, K1: manure 7,5 kg/5m2, K2: manure 15 kg/5m2 and the second factor was NPK (M) fertilizer which consists of M0: NPK fertilizer 0 g/5m2, M1: NPK fertilizer 37,5 g/5m2, M2: NPK fertilizer 75 g/5m2 and M3: NPK fertilizer 112,5 g/5m2. The growth variables measured were height plant and number of leaves of third defoliation. The results of the analysis of variance showed that the interaction between the combination of manure and NPK was not significant effect (P>0.05), while the manure application was highly significant effect (P<0.01) on height plant and number of leaves, NPK fertilizer was significant effect (P<0.05) of height plant and number of leaves of dwarf grass. The single effect of manure and NPK can significantly increased height plant and number of leaves. Interaction between manure and NPK was not significant effect on height plant and number of leaves dwarf grass. Keywords: odot grass, manure, NPK, growth